The impact of admission neutrophil-to-platelet ratio on in-hospital and long-term mortality in patients with infective endocarditis - Wei, Xue-biao; Liu, Yuan-hui; He, Peng-cheng; Yu, Dan-qing; Tan, Ning; Zhou, Ying-ling; Chen, Ji-yan (Clinical chemistry and laboratory medicine, 2017)
Infective endocarditis (IE) is associated with increased neutrophil and reduced platelet counts. We assessed the relationship between the neutrophil-to-platelet ratio (NPR) on admission and adverse outcomes in patients with IE. Patients diagnosed with IE between January 2009 and July 2015 (n=1293) were enrolled, and 1046 were finally entered into the study. Study subjects were categorized into four groups according to NPR quartiles: Q1<18.9 (n=260); Q2: 18.9-27.7 (n=258); Q3: 27.7-43.3 (n=266); and Q4>43.3 (n=262). Cox proportional hazards regression was performed to identify risk factors for long-term mortality; the optimal cut-off was evaluated by receiver operating characteristic curves. Risk of in-hospital death increased progressively with NPR group number (1.9 vs. 5.0 vs. 9.8 vs. 14.1%, p<0.001). The follow-up period was a median of 28.8 months, during which 144 subjects (14.3%) died. Long-term mortality increased from the lowest to the highest NPR quartiles (7.6, 11.8, 17.4, and 26.2%, respectively, p<0.001). Multivariate Cox proportional hazard analysis revealed that lgNPR (HR=2.22) was an independent predictor of long-term mortality. Kaplan-Meier survival curves showed that subjects in Q4 had an increased long-term mortality compared with the other groups. Increased NPR was associated with in-hospital and long-term mortality in patients with IE. As a simple and inexpensive index, NPR may be a useful and rapid screening tool to identify IE patients at high risk of mortality.